Direct Observation of Reversible Magnesium Ion Intercalation into a Spinel Oxide Host. (17th April 2015) - Kim, Chunjoong; Phillips, Patrick J.; Key, Baris; Yi, Tanghong; Nordlund, Dennis; Yu, Young‐Sang; Bayliss, Ryan D.; Han, Sang‐Don; He, Meinan; Zhang, Zhengcheng; Burrell, Anthony K.; Klie, Robert F.; et al.
<x xml:space="preserve">Abstract</x> Direct evidence of Mg2+ intercalation into a spinel‐type Mn2O4 is provided. By combining tools with different sensitivities, from atomic‐resolution X‐ray spectroscopy to bulk X‐ray diffraction, it is demonstrated that Mg2+ reversibly occupies the tetrahedral sites of the spinel structure through the reduction of Mn when the electrochemical reaction is performed.